2009
DOI: 10.1099/ijs.0.003228-0
|View full text |Cite
|
Sign up to set email alerts
|

Planotetraspora thailandica sp. nov., isolated from soil in Thailand

Abstract: A Gram-positive-staining, filamentous bacterial strain that developed cylindrical sporangia containing four oval-to rod-shaped spores at the ends of short sporangiophores on branched aerial mycelium was isolated from tropical rainforest soil near a hot spring. The cell-wall peptidoglycan contained meso-diaminopimelic acid, glutamic acid and alanine as cell-wall amino acids; the whole-cell hydrolysate contained rhamnose, madurose, glucose, galactose and 3-Omethylmannose as whole-cell sugars. The predominant men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 35 publications
0
63
0
Order By: Relevance
“…from the organic layer on the soil surface and kept at 4 C. The sample was dried at room temperature for 10 days, then dry-heated at 100 C for 1 h. The dried sample was treated using the flooding method of Suzuki (2001). The organism was isolated on soil extract agar (Suriyachadkun et al, 2009) supplemented with 25 mg nalidixic acid l À1 , 50 mg cycloheximide l À1 and 1 mg terbinafine l À1 , then incubated at 28 C for 30 days. The isolate was purified on soil extract agar.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…from the organic layer on the soil surface and kept at 4 C. The sample was dried at room temperature for 10 days, then dry-heated at 100 C for 1 h. The dried sample was treated using the flooding method of Suzuki (2001). The organism was isolated on soil extract agar (Suriyachadkun et al, 2009) supplemented with 25 mg nalidixic acid l À1 , 50 mg cycloheximide l À1 and 1 mg terbinafine l À1 , then incubated at 28 C for 30 days. The isolate was purified on soil extract agar.…”
mentioning
confidence: 99%
“…The pure culture was preserved in glycerol (10 %, v/v) at À80 C and in a liquid-dried form for longterm storage. Type strains of every species of the genus Planomonospora were used in this study for comparison of physiological, morphological and chemotaxonomic properties and DNA-DNA hybridization.Morphological characteristics of mycelia and sporangia of strain A-T 11038 T were determined by light microscope (model CX 31; Olympus) with a 50Â long working distance objective lens (model SLMPLN50X; Olympus) and scanning electron microscope (model JSM-5410 LV; JEOL) using cultures grown on soil extract agar (Suriyachadkun et al, 2009) at 28 C for 14-21 days. Cultures for scanning electron microscopy were prepared as described by Itoh et al (1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological characteristics of strain BR3-1 T grown on modified soil extract agar (Suriyachadkun et al, 2009) were observed using light and scanning electron microscopy (model JSM-5410 LV; JEOL). The preparation of scanning electron microscopic samples was as described previously (Thawai et al, 2005).…”
mentioning
confidence: 99%
“…Morphological characteristics of strain A-T 6646 T grown on modified soil extract agar (Suriyachadkun et al, 2009) at 28 u C for 7-14 days were observed with a light microscope (model CX 31; Olympus) with a 640 long working distance objective lens (model LUCPLFLN40XRC; Olympus) and a scanning electron microscope (model JSM-5410 LV; JEOL). Samples on modified soil extract agar for scanning electron microscopy were prepared as described by Itoh et al (1989).…”
mentioning
confidence: 99%